Does Early Childhood Vaccination Protect Against COVID-19? - Sidiq, Karzan R.; Sabir, Dana Khdr; Ali, Shakhawan M.; Kodzius, Rimantas (Frontiers in Molecular Biosciences, 2020)
The coronavirus disease 2019 (COVID-19) has recently categorized as a pandemic disease due to its high morbidity and mortality in several countries around the globe. The disease is caused by SARS-coronavirus-2 (SARS-CoV-2) that targets the respiratory system of the human being. The published data shows that children, unlike adults, are less susceptible to contracting COVID-19. This article aims to investigate why children constitute a minor group among hospitalized COVID-19 patients. Here, we hypothesize that the routine childhood vaccination may provide broad neutralizing antibody against numbers of diseases, including COVID-19. Homologous sequence searching for the Spike (S) protein of SARS-CoV-2 (PDB: 6VSB) was shown a short amino acid sequence similarity to the measles virus glycoprotein F1 Fusion protein (PDB: 5YXw_B) and rubella viruses. Therefore, the humoral immunity that created through routine vaccination could provide children with advantageous protection against COVID-19.